Computed Tomography–Guided Spinal Biopsy in Suspected Infective Spondylodiscitis: An Institutional Review of Its Utility - Ravichandran, Raj Chendur Abhishek; Amritanand, Rohit; Moses, Vinu; Kandagaddala, Madhavi; Krishnan, Venkatesh; David, Kenny Samuel; Arockiaraj, Justin; Kulasekaran, Harini; Ganesan, Maya Pavalasseril; Prabhu, Anne Jennifer; Keshava, Shyamkumar Nidugala (Indian Journal of Radiology and Imaging, 2023)
Background Infectious spondylodiscitis is a debilitating condition and evidence-based medicine dictates confirming the diagnosis before treatment. Computed tomography–guided spinal biopsy plays a major role and hence we would like to determine its utility in current clinical practice.Purpose The purpose of this study is to determine the percentage of confirmatory positives of CT-guided spinal biopsy in patients who were clinicoradiologically diagnosed with infectious spondylitis.Material and Methods A retrospective analysis of patients who underwent CT-guided biopsy for suspected infectious spondylodiscitis from 2017 to 2021 in a tertiary medical center was done. The data were filtered and obtained from the electronic database of the institution.Results In all, 259 patients underwent CT-guided biopsy of the spine. The procedure provided confirmatory results in 149 (57.5%) biospecimens. Histopathology examination was confirmatory in 95 (36.6%) of the 241 biospecimens sent. The Mycobacteria Growth Indicator Tube (MGIT) was confirmatory in 51 (19.9%) of the 250 biospecimens sent and drug resistance was seen in 6/51 (11.7%) biospecimens. Xpert TB provided confirmatory results in 72 (27.8%) of the 254 biospecimens sent and rifampicin resistance was seen in 16/72 (22.2%) biospecimens. Bacterial culture was confirmatory in 29 (11.2%) of the 250 biospecimens sent. The complication documented in this study was 0.3%.Conclusion CT-guided spinal biopsy for suspected vertebral osteomyelitis is a safe and effective minimally invasive procedure. It demonstrates a positive yield in more than half of the patients. Knowing the outcome, the patients can be appropriately counseled prior to the procedure. CT-guided biopsy results were affected by prior administration of ATT (antitubercular therapy) in suspected tuberculous spondylitis patients.
Keywords: spine biopsy; CT; infectious spondylodiscitis; tuberculous spondylodiscitis; pyogenic spondylodiscitis; antitubercular therapy